2012
DOI: 10.1039/c2jm11739h
|View full text |Cite
|
Sign up to set email alerts
|

Calcium phosphate nanoparticle mediated genetic transformation in plants

Abstract: We have produced ultra-small sized (20-50 nm diameter) calcium phosphate (CaP) nanoparticles encapsulating a reporter gene, pCambia 1301. The material in the nanoparticles is of crystalline nature having a hydroxyapatite structure as revealed from the XRD pattern. The maximum loading of pCambia 1301 in the nanoparticles and the pH-dependent dissolution of CaP nanoparticles were studied using gel electrophoresis. DNA is highly protected in the cell from cellular nucleases when it is encapsulated into the CaP na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(42 citation statements)
references
References 36 publications
0
40
0
Order By: Relevance
“…Recently, there has been much interest in the use of nanomaterials as delivery vehicles for biomolecules into plant cells, especially for plant genetic transformation . Nanoparticle‐based delivery methods have the potential of overcoming the current limitations in plant genome engineering, with unique advantages such as high throughput, low cytotoxicity, and wide applicability to a range of plant species . Furthermore, when bound to nanoparticles, biomolecular cargos are shielded from enzymatic degradation within biological environments and can be potentially controlled to target specific organelles or tissues .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there has been much interest in the use of nanomaterials as delivery vehicles for biomolecules into plant cells, especially for plant genetic transformation . Nanoparticle‐based delivery methods have the potential of overcoming the current limitations in plant genome engineering, with unique advantages such as high throughput, low cytotoxicity, and wide applicability to a range of plant species . Furthermore, when bound to nanoparticles, biomolecular cargos are shielded from enzymatic degradation within biological environments and can be potentially controlled to target specific organelles or tissues .…”
Section: Introductionmentioning
confidence: 99%
“…Further in vivo study in higher mammals is required to make this nano-tetracycline functional to combat deadly pathogenic multiple antibiotics-resistant bacteria, challenging the major cause of A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT 22 death in tropical countries. The results of our ongoing study on the survivability of Shiigellainjected mice by Tet-CPNP, administered through oral dose, are quite encouraging.…”
Section: Resultsmentioning
confidence: 99%
“…ACCEPTED MANUSCRIPT 4 reasons behind choosing CPNP -i) tetracycline has higher affinity of chelation with divalent metal ions [16,17] and so, it can easily bind with CPNP, ii) CPNP is used as a potential carrier of DNA [18,19,20,21,22], RNA [23,24], proteins [25,26] and various therapeutic drugs [27,28,29,30,31] into different cells and iii) calcium phosphate, being a principal component of human bones and teeth, is highly biocompatible and biodegradable [32,33]. Here, we report that the Tet-CPNP killed different multi-drug resistant diarrhea-causing bacteria viz., Escherichia coli, Salmonella kentuckey and Shigella flexneri in vitro; in vivo killing of Shigella flexneri that infected Zebra fish larvae was also observed.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Up to now, only calcium phosphate nanoparticles and poly dendrimer (DNA vector),showed that particles could be entered into plants through simple co-culture methods and works as carriers for gene delivery without any additional assistance, and high transient delivery efficiency could be obtained [34]. However, this method was cost effective and should be developed further.…”
Section: Microprojectile Bombardmentmentioning
confidence: 99%